OVULE RESCUE IN PEACHES: INCUBATION PERIOD - RASEIRA, Maria do Carmo Bassols; EINHARDT, Patrícia Milech (Scientia Agraria, 2010)
Success with immature embryos has been achieved since 1936. However, as smaller is the embryo more complex and difficult is to have a desirable survival percentage. The objective of this work was to check the period of time that seeds should be kept in the culture media at 22 ±1 °C, before being submitted to the embryo culture procedure. The effect of keeping the fruits for a week in cold room, previously to the ovule rescue, was also evaluated. Results showed that the time for ovule incubation at 22 ±1 °C, can be up to nine weeks but better three to five weeks. The limiting factor is related to seed contamination by pathogens. It is also possible to have success with ovule rescue of embryos of fruits kept for one week in cold room, as long as the time, the ovule incubation period, is not superior to three or four weeks.